Application of the Requirements of (the Context of Organization & Operation) Case Study in the Central Bank of Iraq - Areej Saeed Khalil Al-Ani; Ali Mudher Abdulbaki Al-Bakri (Journal of Madenat Alelem University College, 2020)
The Importance of research as a contribution to diagnosis to reality of the application of the context of organization and operation in the central bank of Iraq within the standard ISO9001: 2015, Which is most needed to apply because the minimum standard of work, while the problem of research is focused on difficulty of application of the standard by taken a sample by the researchers, Which is (The Context of Organization and the operation) to be applied in the Central Bank of Iraq using checklists. The Researchers concluded a set of conclusions. Most notably the fact that the standard ISO9001: 2015 is the first limit for beginning of the work, and is adopted by the organization in order to distinguish its services from competitors and start work for excellence.